The Expressive Illocutionary Act Used By The Main Character In â€œPersuasionâ€ Movie - Made Adis Indayanti; Ida Ayu Mela Tustiawati (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study analyzes the Attitude of expressive illocutionary acts found in the movie script of "Persuasion." Data used in this study could be considered qualitative data, and it was analyzed using a qualitative descriptive method. Explaining the sentence in the data allows a precise analysis using the theory from Searle (1979) and Halliday and Hasan (1985). The findings show that there are 13 Sentences of expressive illocutionary acts. The result shows that the most dominant type used by the main character is expressive of Attitude, which contains nine utterances. The character in The 'Persuasion' movie mostly expressed feelings about disagreement, so they most used an expressive attitude. There should be more research on the expressive illocutionary act with different theories and methods. Hopefully, this research can be helpful in education and help further research.